Valor econômico da água para irrigação no semi-árido cearense - Pinheiro, José César Vieira (1998)
This study is the result of an attempt to evaluate the current irrigation water distribution and price setting criteria in a irrigation project located in the semi-arid region in the State of Ceará, Brazil. The value of water was calculated using estimated short-run demand curves. These curves were obtained from empirically determined production functions for selected crops. The empirical part of the study was conducted in the `Guru-Paraipaba' Irrigation Project using data collected for the 1995/96 crop season. This work also estimates the indirect effect of a few social-economic characteristics of the farmers, such as education, age and the level of technology on the production. In the scheme prevailing, a public company distributes the water according to a given, per hectare, average consumption and the rate is determined to a level that recovers the operational costs. There is no exclusivity in the water use. The returns of the different crops as well as the farmers' willingness to pay are not considered in the allocative criteria. The results from a simulation show that crops prices directly affect the water value. Thus, considering that the water is scarce in the semi-arid region, an alternative to increase its value could be obtained through the irrigation of high price crops. The study shows that the efficient rate for water in the project would be R$ 140.61 / thousand cubic meter. The coconut would be strongly stimulated through the redistribution of water from sugar-cane and papaya. The comparison of the actual water use with the distribution suggested by the model indicates that 36.6% of the water is being allocated in the wrong crop. This is an indication of the current level of inefficiency. If each crop received the optimal quantity of water, the gross production value would increase significantly. The receipt generated by the payment for the water would be more than enough to cover the cost of operation and maintenance. This study is particularly relevant in the semi-arid region of the State of Ceara, where the water is scarce and the agriculture depends on the irrigation in the periods. This confirms the results obtained in several studies of economic evaluation of irrigation projects in the northeast region of Brazil. Many of them show modest returns and did not adequately remunerate the factors of production used.